Creatives on creativity : Steve Brouwers. - Brouwers, Steve, ....- (Antwerpen : LUSTER, 2021)
In Creatives for Creativity Steve Brouwers (creative director at SBS) interviews 42 makers - painters, photographers, graphic designers, conceptual artists, furniture designers, video artists, advertisers - from all around the world. He asks them about their childhood, their creative process, their inspirations and their most memorable achievements. The question that kicks off every interview - What is creativity to you? - results in an inspiring collection of personal conversations that provide an extraordinary insight into the artists' minds. Interviews with: Nel Aerts, Alain Biltereyst, Conrad Botes, Jenny Brosinski, Tad Carpenter, Emily Forgot, Matt Clark, Jim Dive, Sue Doeksen, Bendt Eyckermans, Paul Fuentes, Harry Gruyaert, Ryan Gander, Tony Gum, Stephanie Hier, Wade Jeffree & Leta Sobierajski, Maira Kalman, Erik Kessels, George Lois, Anna Mac, Debbie Millman, Jonathan Monk, Mr Bingo, Morag Myerscough, Navid Nuur, Gemma O'Brien, Max Pinckers, Pixie Pravda, Kay Rosen, Stefan Sagmeister, Paula Scher, Yuko Shimizu, Sammy Slabbinck, John Stezaker, Charline Tyberghein, David Uzochukwu, Joris Van De Moortel, Anne-Mie Van Kerckhoven, Dominic Wilcox, Matt Willey and Shawna X.
Keywords: Creativiteit; Kunstenaars